Designing monetary infrastructures for the common good: Reciprocity and sustainability in parallel currencies - Massó, Matilde (Zeitschrift für Theoretische Soziologie, 2026)
This article examines the hybrid nature of money as an institutional arrangement co-produced by public and private actors, focusing on how monetary design shapes the organisation of value, labour and access to income. It situates monetary reform within a relational and regenerative conception of sustainability, understood as an institutional property of how societies organise economic coordination over time within biophysical constraints. The article critically assesses the limitations of existing proposals for monetary change, their conceptual foundations and the analytical gaps that limit their capacity to fulfil the economic and institutional functions conventionally attributed to money. It then advances the design of a complementary currency, Twin Money (TMy), intended to monetise socially recognised forms of voluntary and care-based labour through state-certified contributions. Drawing on reciprocity as a principle of economic integration, the proposal redefines money’s core functions by linking monetary issuance to socially valuable activity rather than to market exchange or financial debt. In doing so, it conceptualises monetary design as a sustainability-relevant institutional choice. TMy is presented as a complementary mechanism capable of expanding access to income, strengthening social inclusion and contributing to more sustainable forms of economic coordination.